Lex Sportiva in Indonesian Sports Law: Autonomy, Independence, and Harmonization with National Law - Dicky Eko Prasetio; Zeidan Izza Al-Farisi (Indonesian Journal of Sports Law, 2024)
The principle of lex sportiva as the main principle in sports law has not yet been regulated in Law No. 11 of 2022 on Sports. The lack of regulation of the lex sportiva principle results in the suboptimal application of the lex sportiva principle in Indonesian sports law. This research aims to analyze the position of the lex sportiva principle in Indonesian sports law and its relevance to the national legal system. This research is a normative legal study that emphasizes a legislative and conceptual approach. The results of this study indicate that sports law, as a new field in legal science, is based on the principle of lex sportiva, which is related to independence, autonomy, and harmonization with the national legal system. The recommendations offered in this study include the need for a revision of Law No. 11 of 2022 on Sports Law by emphasizing the position of the lex sportiva principle in Indonesian sports law, as well as the need for an understanding of the lex sportiva principle in the organization of sports, including making the lex sportiva principle a part of legal considerations for judges in the Supreme Court and the Constitutional Court when adjudicating disputes related to sports aspects.